Regulation of astrocyte activity and immune response on graphene oxide-coated titanium by electrophoretic deposition - Han, Yong-Soo; Jang, Jun-Hwee; Lee, Won-Seok; Oh, Jun-Sung; Lee, Eun-Jung; Yoon, Bo-Eun (Frontiers in Bioengineering and Biotechnology, 2023)
Astrocytes play crucial role in modulating immune response in the damaged central nervous system. Numerous studies have investigated the relationship between immune responses in astrocytes and brain diseases. However, the potential application of nanomaterials for alleviating neuroinflammation induced by astrocytes remains unexplored. In this study, we utilized electrophoretic deposition (EPD) to coat graphene oxide (GO) onto titanium (Ti) to enhance the bioactivity of Ti. We confirmed that GO-Ti could improve cell adhesion and proliferation of astrocytes with upregulated integrins and glial fibrillary acidic protein (GFAP) expression. Moreover, we observed that astrocytes on GO-Ti exhibited a heightened immune response when exposed to lipopolysaccharide (LPS). Although proinflammatory cytokines increased, anti-inflammatory cytokines and brain-derived neurotrophic factors involved in neuroprotective effects were also augmented through nuclear localization of the yesassociated protein (YAP) and nuclear factor kappa B (NF-κB). Taken together, GO-Ti could enhance the neuroprotective function of astrocytes by upregulating the expression of anti-inflammatory cytokines and neuroprotective factors with improved cell adhesion and viability. Consequently, our findings suggest that GO-Ti has the potential to induce neuroprotective effects by regulating cell activity.